Ovicidal Potential of Ethanol Extract of Cherry Leaves (Muntingia calabura L.) against Aedes aegypti Mosquito: Potensi ovisida Ekstrak Etanol Daun Kersen (Muntingia calabura L.) terhadap Nyamuk Aedes aegypti - Lubis, Lulu Elsarah; Rosa, Emantis; Pratami, Gina Dania; Ernawiati, Eti (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2025)
Dengue fever is one of the viral diseases transmitted through arthropods and is still a significant health problem worldwide. Dengue virus is transmitted by Aedes aegypti mosquitoes from one human to another through blood sucking. These mosquitoes usually live and lay eggs in habitats close to stagnant water. The usual efforts to control Ae. aegypti are using natural and synthetic chemicals. Compounds to control Ae. aegypti eggs are called ovicides. One of the natural ingredients that is thought to contain natural chemicals that have the potential to be used as an ovicide is cherry leaves (Muntingia calabura L.). This study aims to determine the potential of the ethanol extract of cherry leaves (M. calabura L.) as an ovicide against Ae. aegypti. Five treatments and four replications were used. The results of this study indicate that the ethanol extract of cherry leaves (M. calabura L.) can potentially be an insecticide for Ae. aegypti at a concentration of 1% and an exposure time of 72 hours.